The Anti-Platonic love in the Sick Rose - Salehi Babamiri, Navid (IJRDO - Journal of Social Science and Humanities Research, 2016)
Plutonic love refers to a kind of love that has no relationship with the sexuality that is completely free of it. In Plato’s dialogue the Symposium it has been examined that how love began and how it has evolved—both sexually and non-sexually. It has been discussed that two kinds of love are Vulgar Eros or earthly love and Divine Eros or divine love. In Wikipedia the extensive definitions have been summarized to show how they are completely different and how each treks its own way. Vulgar Eros is nothing but mere material attraction towards a beautiful body for physical pleasure and reproduction, which Plato does not agree. Divine Eros begins the journey from physical attraction i.e. attraction towards beautiful form or body but transcends gradually to love for Supreme Beauty. This paper also tries to shed light on the Anti-Platonic love that both Marvel and Blake have it done through symbols and other literary devices in the frame of their work.